2022
DOI: 10.1139/cjss-2020-0160
|View full text |Cite
|
Sign up to set email alerts
|

Biochar mitigation of allelopathic effects in three invasive plants: evidence from seed germination trials

Abstract: Many invasive species show allelopathic effects that contribute to competitive impacts on native vegetation for which few control measures exist. We investigated the potential for pyrolized organic material used as a soil amendment (“biochar”) to sorb allelochemicals and mitigate allelopathic effects on seed germination and early seedling development in three common invasive plants in Canada, garlic mustard (Alliaria petiolata), tree of heaven (Ailanthus altissima) and yellow sweetgrass (Melilotus officinalis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…This suggests that increased growth in response to biochar additions was not due to an increase in soil nutrient concentrations, but rather an alleviation of allelopathic effects. The primary mechanism for the reduced allelopathic effects is almost certainly the sorption of allelochemicals, as demonstrated in prior laboratory experiments (Bieser et al, 2022;Hall et al, 2014;Sujeeun & Thomas, 2017). Woodfeedstock biochars sorb a wide variety of polyaromatic hydrocarbons with chemical structures similar to common allelochemicals such as juglone, with aromatic rings and terminal carboxyl and methyl functional groups being most important in the sorption process (Zhou et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This suggests that increased growth in response to biochar additions was not due to an increase in soil nutrient concentrations, but rather an alleviation of allelopathic effects. The primary mechanism for the reduced allelopathic effects is almost certainly the sorption of allelochemicals, as demonstrated in prior laboratory experiments (Bieser et al, 2022;Hall et al, 2014;Sujeeun & Thomas, 2017). Woodfeedstock biochars sorb a wide variety of polyaromatic hydrocarbons with chemical structures similar to common allelochemicals such as juglone, with aromatic rings and terminal carboxyl and methyl functional groups being most important in the sorption process (Zhou et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…Allelopathy increases the negative effects of many invasive species and makes them more difficult to manage, but BC is a promising tool against allelopathic invasive species (Sujeeun & Thomas, 2022) due to its ability to sorb and reduce the bioavailability of a wide range of organic compounds (Hall et al, 2014; Kumar et al, 2020). Recent laboratory trials have shown that BCs have the potential to alleviate the inhibitory effects of a wide range of allelopathic invasive plants (Bieser et al, 2022; Shen et al, 2020; Sujeeun & Thomas, 2017). BC is a more uniform type of pyrolyzed biomass compared with charcoal produced in wildfires, but both forms of pyrogenic carbon (PyC) have similar sorptive properties (Qi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the capacity of biochar to mitigate the inhibitory effects of certain invasive species may be less pronounced when larger allelopathic compounds are involved. For example, biochar was only able to marginally alleviate the allelopathic effects of Ailanthus altissima, possibly due to steric effects that reduce sorption of large polyaromatic molecules [34]. Biochar appears to be a viable tool for combatting several tropical allelopathic invasive species, but a combination of laboratory and field studies is necessary to examine the properties and dosages of biochar that will optimize sorption of allelochemicals and native tree growth in invaded ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar-or charcoal used as soil amendment-has been widely hailed for its potential to enhance productivity and sequester carbon [31], with a recent focus on its capacity to sorb soil contaminants [32]. Research on biochar mitigation of allelopathy, however, has been limited to laboratory and greenhouse trials [24,[33][34][35]. Long-term field studies on allelopathic interactions are scarce [36,37] and none have examined the capacity of biochar to increase native tree growth in forest areas invaded by allelopathic species.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanisms for climate change mitigation of biochar are a molecular structure dominated by aromatic carbon blocks that make it more resistant to microbial decomposition, allowing it to persist in soil for thousands of years and potentially curbing greenhouse gas emissions (Messiga et al 2022a(Messiga et al , 2022bDeng et al 2022). Biochar physical and chemical properties have become useful in site restoration projects in forest ecosystems and urban soils due to its ability to adsorb and immobilize organic chemicals (Bieser et al 2022). Manuscripts in this special issue help bridge our current knowledge gap and recognize the contribution of biochar in temperate agricultural soils as a way forward to sustainable crop productivity, healthy soils, and climate change mitigation.…”
Section: Introductionmentioning
confidence: 99%